ANALYTIC CAUSATIVES IN JAVANESE: A LEXICAL- FUNCTIONAL APPROACH - Agus Subiyanto (Master Program in Linguistics, Diponegoro University, 2013)
Analytic causatives are the type of causatives formed by separate predicates expressing the cause and the effect, that is, the causing notion is realized by a word separate from the word denoting the caused activity. This paper aims to discuss the forms and syntactic structure of analytic causatives in Javanese. To discuss the syntactic structure, the theory of lexical functional grammar (LFG) is employed. The data used in this study is the „ngoko‟ level of Javanese of the Surakarta dialect. By using a negation marker and modals as the syntactic operators to test mono- or bi-clausality of analytic causatives, the writer found that analytic causatives in Javanese form biclausal constructions. These constructions have an X-COMP structure, in that the SUBJ of the second verb is controlled by the OBJ of the causative verb (N)gawe „make‟. In terms of the constituent structure, analytic causatives have two kinds of structures, which are V-cause OBJ X-COMP and V-cause X-COMP OBJ. Kausatif analitik adalah tipe kausatif yang dibentuk oleh dua predikat atau dua kata terpisah untuk mengungkapkan makna sebab dan akibat, yakni makna sebab direalisasikan oleh kata yang berbeda dengan kata yang menyatakan makna akibat. Tulisan ini membahas bentuk dan struktur sintaksis kausatif analitik dalam bahasa Jawa. Untuk menjelaskan struktur sintaksis digunakan teori Tata Bahasa Leksikal Fungsional. Data yang digunakan dalam penelitian ini adalah bahasa Jawa dialek Surakarta ragam ngoko. Dengan menggunakan alat uji pemarkah negasi dan penggunaaan modalitas, penulis menemukan bahwa kausatif analitik dalam bahasa Jawa membentuk struktur biklausa. Konstruksi ini memiliki struktur X-KOMP, yakni SUBJ dari verba kedua dilesapkan dan dikendalikan oleh OBJ dari verba kausatif (N)gawe „membuat‟. Dalam struktur konstituen, analitik kausatif memiliki dua macam bentuk, yakni V-kuasatif OBJ X-COMP and V-kausatif X-COMP OBJ.